Prevalence of HIV and HIV–Hepatitis B Co‐Infection in Hepatocellular Carcinoma Patients in the Gambia, 2012–2019: A Prospective Cohort Study - Sheikh Omar Bittaye; Abubacarr Kambi; Momodou A. I. Tekanyi; Saydiba Tamba; Lamin Bojang; Lamin Sanneh; Momodou Musa Sisawo; Abdoulie Jatta; Gibril Fatty; Adam Jeng; Momodou Salieu Jallow; Ousman Leigh; et al. (Health Science Reports)
ABSTRACT Background HIV–hepatitis B co‐infection rapidly progresses to fibrosis, cirrhosis, and HCC and has a poor prognosis. The study therefore assesses the prevalence of HIV and HIV–hepatitis B co‐infection in the Gambia. Methods From June 2012 to September 2019, patients with confirmed diagnosis of HCC were enrolled. All patients medical history, ultrasound scan, fibroscan and laboratory details were collected. Results The study recruited 476 HCC patients. The prevalence of HIV amongst the HCC patient was 21 (4.4%), and this was higher in males, 19 (4.9%), than in females, 2 (2.2%). The HCC patients with Hepatitis B only were 319 (67.2%). Those HCC patients with HIV‐hepatitis B co‐infection were 17 (3.6%). HCC patients with HIV–hepatitis B co‐infection were much younger and more likely to be male as compared to HCC patients with Hepatitis B only or HCC patients with negative HIV–hepatitis B. There was no difference between the median survivals of the three HCC patient groups. Conclusions The prevalence of HIV in HCC patients is higher than in the general population. HIV–hepatitis B disproportionately affects young men, but there was no difference in survival. This study therefore confirms the need to have an integrated HIV–hepatitis B services in Hepatology clinics or screening programs in the Gambia to early detect co‐infections, especially in young men and start them on treatment to prevent chronic liver disease complications and improve prognosis.